Diethylenetriamine-mediated self-assembly of three-dimensional hierarchical nanoporous CoP nanoflowers/pristine graphene interconnected networks as efficient electrocatalysts toward hydrogen evolution. Issue 10 (25th October 2017) - Fan, Xiuling; Wang, Xiaoyan; Yuan, Weiyong; Li, Chang Ming
Abstract : A 3D hierarchical nanoporous CoP nanoflowers/graphene interconnected network was synthesized via DETA-mediated self-assembly, showing superior HER catalytic performance. Abstract : Highly active, durable, and low-cost hydrogen evolution reaction (HER) catalysts are critical for large-scale energy storage in the form of hydrogen through water splitting but their fabrication presents great challenges. Herein we report the synthesis of a novel 3D hierarchical nanoporous CoP nanoflowers/pristine graphene interconnected network structure via diethylenetriamine (DETA)-mediated self-assembly, in which DETA promoted the uniform dispersion of graphene and the nucleation of the CoP precursor on graphene, the seed aggregation facilitated the formation of nanoflowers and a 3D network, and the gas release during the low-temperature phosphidation produced nanopores inside the nanoflowers. This nanoarchitecture shows an onset potential of −0.014 V, an overpotential of 98.1 mV to achieve 10 mA cm −2, a Tafel slope of 40.9 mV dec −1, and an exchange current density of 0.119 mA cm −2 . The onset overpotential, overpotential to achieve 10 mA cm −2, and Tafel slope are all among the lowest reported for non-noble metal hydrogen evolution reaction (HER) catalysts, and the exchange current density also compares favorably to those of most reported HER catalysts. In addition, the catalyst exhibits excellent durability with negligible loss in current density after 2000 cyclic voltammetry (CV) cycles (+0.01 to −0.17 V vs. the RHE, at a scan rate of 100 mV s −1 ) or 23.5 h of chronoamperometric measurement at an overpotential of 98.1 mV, and a high faradaic efficiency of close to 100%. This work not only creates a high-performance and inexpensive HER electrocatalyst by utilizing the great advantages of 3D hierarchically nanostructured networks, but also develops a facile and economical strategy for the self-assembly of hierarchical nanostructures and offers scientific insight into its mechanism.